EDNA metabarcoding of log hollow sediments and soils highlights the importance of substrate type, frequency of sampling and animal size, for vertebrate species detection. Issue 4 (9th May 2022) - Ryan, Ethan; Bateman, Philip; Fernandes, Kristen; van der Heyde, Mieke; Nevill, Paul
Abstract: Fauna monitoring often relies on visual monitoring techniques such as camera trapping, which have biases leading to underestimates of vertebrate species diversity. Environmental DNA (eDNA) metabarcoding has emerged as a new source of biodiversity data that may improve biomonitoring; however, eDNA‐based assessments of species richness remain relatively untested in terrestrial environments. We investigated the suitability of fallen log hollow sediment as a source of vertebrate eDNA, across two sites in southwestern Australia—one with a Mediterranean climate and the other semi‐arid. We compared two different approaches (camera trapping and eDNA metabarcoding) for monitoring of vertebrate species, and investigated the effect of other factors (frequency of species, timing of visits, frequency of sampling, and body size) on vertebrate species detectability. Metabarcoding of hollow sediments resulted in the detection of higher species richness in comparison (29 taxa: six birds, three reptiles, and 20 mammals) to metabarcoding of soil at the entrance of the hollow (13 taxa: three birds, two reptiles, and eight mammals). We detected 31 taxa in total with eDNA metabarcoding and 47 with camera traps, with 14 taxa detected by both (12 mammals and two birds). By comparing camera trap data with eDNA read abundance, we were able to detect vertebrates through eDNA metabarcoding that had visited the area up to two months prior to sample collection. Larger animals were more likely to be detected, and so were vertebrates that were identified multiple times in the camera traps. These findings demonstrate the importance of substrate selection, frequency of sampling, and animal size, on eDNA‐based monitoring. Future eDNA experimental design should consider all these factors as they affect detection of target taxa. Abstract : We compared different monitoring approaches (eDNA metabarcoding and camera traps), and terrestrial substrates (soil, tree hollow sediment). We also investigate the effect of other factors (visitation frequency and timing, animal size) on vertebrate detectability. Our results demonstrate the importance of substrate selection, frequency of sampling, and animal size, for eDNA based surveys.